Ligand-free nano-grain Cu2SnS3 as a potential cathode alternative for both cobalt and iodine redox electrolyte dye-sensitized solar cells. Issue 38 (15th September 2016) - Liu, Feng; Hu, Shuanglin; Ding, Xunlei; Zhu, Jun; Wen, Jian; Pan, Xu; Chen, Shuanghong; Nazeeruddin, Md. K.; Dai, Songyuan
Abstract : Both theoretical calculations and electrochemical measurements suggest the applicability of Cu2 SnS3 as an efficient alternative catalyst in DSSCs. Abstract : Tetragonal phase Cu2 SnS3 (CTS) in the form of nano-grain thin film serves as an efficient inexpensive electrocatalyst alternative to the commonly used Pt in dye-sensitized solar cells (DSSCs) exhibiting remarkable electrochemical stability and electrocatalytic activity for both cobalt (Co(iii )/Co(ii ))- and iodine (I3 − /I − )-based redox electrolytes. In this study, the catalytic activity of the CTS electrode was first theoretically predicted via first-principles calculations using density functional theory. Electrochemical measurements confirm their superior catalytic performance to Pt toward both the reduction of I3 − and Co 3+ . Significantly, ensuing DSSCs with the CTS cathode demonstrate a photovoltaic efficiency of 10.26%, higher than that with Pt (9.31%). Through impedance spectra, we also show that increasing the amount of CTS loading can further enhance its apparent catalytic performance. However, improving the crystallization of the CTS film by increasing the annealing temperature to a certain degree will only reduce its activity.